Journal of Human Sport and Exercise - 2021 - Spring Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc4.51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical activity on COVID-19 symptoms: A narrative review

Abstract: In 2019, a new condition caused by the COVID-19, became a global pandemic, presenting a disparate symptomatological picture. The immune response to the virus depends on multiple factors, making the practice of physical exercise an important enhancer of the immune system, but it is unknown what effects it could have on the very different symptoms. In order to achieve and summarize the most outstanding information on the influence of the different types and parameters of physical exercise on the immune system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This review aimed to investigate the existing evidence in the last five years (January 2016 through December 2021), regarding the immunological response of different physical exercise modalities in the population aged 25 to 84 years, identified with the highest number of confirmed cases of COVID-19, declared in the WHO report n°198 of the World Health Organization (2) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review aimed to investigate the existing evidence in the last five years (January 2016 through December 2021), regarding the immunological response of different physical exercise modalities in the population aged 25 to 84 years, identified with the highest number of confirmed cases of COVID-19, declared in the WHO report n°198 of the World Health Organization (2) .…”
Section: Discussionmentioning
confidence: 99%
“…In late 2019, a new condition caused by SARS-CoV-2 was reported in Wuhan, China, causing a global pandemic problem (1,2) . Autopsies of patients who died from COVID-19 identified that the virus invades mainly the lungs, but also affects the cardiovascular system, the liver, the kidneys, and the coagulation system (3) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation